1993
DOI: 10.1002/glia.440080108
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of metallothionein in the human central nervous system

Abstract: The distribution of metallothionein (MT), a metal-binding protein, was examined immunohistochemically in the normal human brain and spinal cord. Paraffin-embedded brain tissue from three patients who had died from a non-neurological disease and were free of histopathological central nervous system alterations were processed. The results of the present study demonstrate that MT is readily detectable in a subgroup of astrocytes in the normal human brain. MT staining is most intense on grey matter astrocytes that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 21 publications
4
34
0
Order By: Relevance
“…In accordance with the present study, most studies on MT expression in CNS describe the absence or scarcity of w x MT-immunopositive neurons 8,42,43,66 . On the other w x hand, by using polyclonal antibodies, Hidalgo et al 28 found MT immunoreactivity in neurons of different rat cerebral and cerebellar areas.…”
Section: Distribution Of Mt In Normal Animalssupporting
confidence: 91%
“…In accordance with the present study, most studies on MT expression in CNS describe the absence or scarcity of w x MT-immunopositive neurons 8,42,43,66 . On the other w x hand, by using polyclonal antibodies, Hidalgo et al 28 found MT immunoreactivity in neurons of different rat cerebral and cerebellar areas.…”
Section: Distribution Of Mt In Normal Animalssupporting
confidence: 91%
“…The findings agreed with those reported in the brain of humans [3,27,28], monkeys [26], rats [14,32] and mice [12,14]. Intense MT-I & -II immunoreactivity was observed in astrocytes in the periventricular area and those around the blood vessels, indicating that MT-I & -II may play a role as a barrier against the toxic substances including metals.…”
Section: Discussionsupporting
confidence: 90%
“…Immunohistochemical localization of MT-I & -II in the brain has been reported in humans [3,27,28], monkeys [26], mice [12,14] and rats [14,32]; MT-I & -II were shown in choroid plexus epithelial cells, ependymal cells, pia mater, and astrocytes in the hypothalamus, hippocampus, cerebral cortex and white matter throughout the brain. With at 5 µm were stained with hematoxylin and eosin (HE) and periodic acid methenamine silver (PAM).…”
Section: Animalsmentioning
confidence: 94%
“…Mammalian MT family consists of four similar but distinct isoforms, designated MT-I, -II, -III and -IV [18,21]. MT-I and -II are expressed in astrocytes in the central nervous system (CNS) [2,16,[22][23][24]27]. It is generally agreed that MTs play important roles in the homeostasis of essential metals including zinc and copper, in the detoxification of heavy metals, and in the scavenging of free radicals [5,11].…”
Section: Animalsmentioning
confidence: 99%